ANALISIS KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR KELAS V - Lilis Sriwati; Aprima Tirsa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the numeracy ability of grade V students of SDN 1 Pinoh Utara in solving the Minimum Competency Assessment (AKM) questions. The research uses a qualitative method with a case study design. The research subjects consisted of 20 students of class V and one homeroom teacher. Data was collected through a 4-question test based on three numeracy indicators and an unstructured interview with the teacher. The results showed that 6 students (30%) were in the high category, 11 students (55%) in the medium category, and 3 students (15%) in the low category. Students are good at using mathematical numbers and symbols and analyzing information in the form of tables. However, the ability to interpret results and make decisions still needs to be improved. These difficulties are influenced by a lack of familiarity with contextual questions, reading skills that are not optimal, and exercises that focus more on calculations. Therefore, numeracy learning needs to be developed through context-based questions, problem-based learning, and the habit of writing down reasons in writing.